2012
DOI: 10.1128/jb.02021-12
|View full text |Cite
|
Sign up to set email alerts
|

LcrV Mutants That Abolish Yersinia Type III Injectisome Function

Abstract: c LcrV, the type III needle cap protein of pathogenic Yersinia, has been proposed to function as a tether between YscF, the needle protein, and YopB-YopD to constitute the injectisome, a conduit for the translocation of effector proteins into host cells. Further, insertion of LcrV-capped needles from a calcium-rich environment into host cells may trigger the low-calcium signal for effector translocation. Here, we used a genetic approach to test the hypothesis that the needle cap responds to the low-calcium sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Second, IpaB has been observed on the tip of needles as part of the tip complex (Ide et al, 2001; Olive et al, 2007; Veenendaal et al, 2007). Most recently, YopD has been detected in purified needle preparations in an LcrV-dependent manner (Ligtenberg et al, 2012). Furthermore, there is a direct correlation between the length of the needle, the distance between the bacteria and host cell, and the ability to inject Yops: the effect of changing the length of the surface adhesin YadA on Y. enterocolitica can be counteracted by changing the length of the needle (Mota et al, 2005).…”
Section: The Making Of An Injectisomementioning
confidence: 99%
“…Second, IpaB has been observed on the tip of needles as part of the tip complex (Ide et al, 2001; Olive et al, 2007; Veenendaal et al, 2007). Most recently, YopD has been detected in purified needle preparations in an LcrV-dependent manner (Ligtenberg et al, 2012). Furthermore, there is a direct correlation between the length of the needle, the distance between the bacteria and host cell, and the ability to inject Yops: the effect of changing the length of the surface adhesin YadA on Y. enterocolitica can be counteracted by changing the length of the needle (Mota et al, 2005).…”
Section: The Making Of An Injectisomementioning
confidence: 99%
“…YopD, but not YopB, has been found in purified needle preparations from Yersinia enterocolitica; however, its location on or within these needles has not be visualized by EM (10,11). While it has been speculated that the YopD in these complexes is due to secreted but insoluble YopD which copurifies with needles (11,12), recent work has also shown that YopD copurifies with LcrVcapped needles (10). YopB and YopD form a hetero-oligomeric pore in mammalian plasma membranes, termed the translocon, and are critical for the formation of a pore through which effector proteins are thought to travel (1,22).…”
mentioning
confidence: 99%
“…A mutant lacking aa 188–207 of LcrV reportedly displays LCR repression, suggesting that the deleted region is necessary for regulation of LCR induction . A recent study determined that the macromolecular structure of LcrV (the needle cap of the injection machinery, as explained later in this review) responds to LCR signals .…”
Section: Lcrv and Its Regulatory Role In Yop Secretionmentioning
confidence: 94%